Protective Effects of N. sativa against the Adverse Effects of Aflatoxicosis in Ducklings - Karn, SKL (Nepal Journal of Science and Technology, 2014)
Aflatoxin produced by Aspergillus flavus toxigenic strain was selected as a potent and widely distributed hepatotoxin that induces much health and economic hazards in animals and humans. A. flavus was cultivated on rice to produce the aflatoxin used in the present study. It was aimed to study the adverse effects of aflatoxin on some biochemical parameters in serum and liver of ducklings as well as to evaluate the possible protective effects of N.sativa crushed seeds against the adverse effects of this. Total proteins, albumin, globulins, alanine aminotransferase (ALT) (EC 2.6.1.1) and aspartate aminotransferase (AST) (EC 2.6.1.2), cholesterol and triacylglycerols were measured in the serum of the test animal. The levels of hepatic malondialdhyde and glutathione level, glutathione S-transferase (GST) (EC: 2.5.1.18) activity, aflatoxin residues and histopathological changes were also measured. The obtained results suggest that the addition of N. sativa to duckling’s ration has a protective effect against aflatoxicosis. The result concluded that aflatoxin had hepatotoxic effects through decrease of total proteins, albumin, glutathione and glutathione S-transferase. In addition, aflatoxin induced histopathological changes of liver of the test animal and residues of aflatoxin were measured. So, we advice to use N. sativa as a feed additive for controlling aflatoxicosis in poultry farm DOI: http://dx.doi.org/10.3126/njst.v14i2.10419 Nepal Journal of Science and Technology Vol. 14, No. 2 (2013) 81-90